DJ-1 as a potential biomarker for the early diagnosis in lung cancer patients. Issue 6 (June 2017) - Han, Binbin; Wang, Jiwen; Gao, Jia; Feng, Shana; Zhu, Yu; Li, Xuexiang; Xiao, Ting; Qi, Jun; Cui, Wei
DJ-1 is a novel oncogene that can transform NIH3T3 cells in cooperation with the activated ras gene. DJ-1 appears to have its greatest effect on tumourigenesis, and it may have a greater impact on early-stage lung cancers. In this study, we proposed to investigate the clinical value of DJ-1 protein in the early diagnosis of lung cancer and compared its diagnostic value with other biomarkers. Preoperative serum DJ-1 levels were measured in 300 lung cancer patients and compared with benign pulmonary disease (n = 44) and healthy volunteers (n = 64). Using tissue microarrays and immunohistochemical analyses, we compared the DJ-1 expression between the primary squamous cell carcinoma tumours and matched metastatic tissues from a lymph node. The baseline preoperative serum DJ-1 of lung cancer patients was significantly higher than that of benign diseases and healthy controls (p < 0.001). In the early-stage subgroup, the median DJ-1 concentration (ng/mL) was significantly higher than that of the advanced stage (12.90 vs 7.75, p < 0.05). Using immunohistochemistry, we observed that the DJ-1 staining intensity was generally weaker and less common in the metastatic tissues compared with that in the primary tumour (McNemar–Bowker Test, p = 0.008). DJ-1 was highly expressed in the early stage of lung cancer, and its expression was significantly decreased after metastasis. Therefore, DJ-1 may be a potential biomarker for the early diagnosis and monitoring of lung cancer metastasis.